Supramolecular architectures of iron phthalocyanine Langmuir-Blodgett films: The role played by the solution solvents - Rubira, Rafael Jesus Gonçalves [UNESP]; Aoki, Pedro Henrique Benites [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2017)
The developing of organic-based devices has been widely explored using ultrathin films as the transducer element, whose supramolecular architecture plays a central role in the device performance. Here, Langmuir and Langmuir-Blodgett (LB) ultrathin films were fabricated from iron phthalocyanine (FePc) solutions in chloroform (CHCl3), dichloromethane (CH2Cl2), dimethylformamide (DMF), and tetrahydrofuran (THF) to determine the influence of different solvents on the supramolecular architecture of the ultrathin films. The UV–vis absorption spectroscopy shows a strong dependence of the FePc aggregation on these solvents. As a consequence, the surface pressure vs. mean molecular area (π-A) isotherms and Brewster angle microscopy (BAM) reveal a more homogeneous (surface morphology) Langmuir film at the air/water interface for FePc in DMF. The same morphological pattern observed for the Langmuir films is preserved upon LB deposition onto solid substrates. The Raman and FTIR analyses indicate the DMF-FePc interaction relies on coordination bonds between N atom (from DMF) and Fe atom (from FePc). Besides, the FePc molecular organization was also found to be affected by the DMF-FePc chemical interaction. It is interesting to note that, if the DMF-FePc leads to less aggregated FePc either in solution or ultrathin films (Langmuir and LB), with time (one week) the opposite trend is found. Taking into account the N-Fe interaction, the performance of the FePc ultrathin films with distinct supramolecular architectures composing sensing units was explored as proof-of-principle in the detection of trace amounts of atrazine herbicide in water using impedance spectroscopy. Further statistical and computational analysis reveal not only the role played by FePc supramolecular architecture but also the sensitivity of the system to detect atrazine solutions down to 10−10 mol/L, which is sufficient to monitor the quality of drinking water even according to the most stringent international regulations.
Keywords: Atrazine; Langmuir; Langmuir-Blodgett; Pollutant; Supramolecular architecture